168k views
1 vote
Factorise and solving

Factorise and solving-example-1
User Ricou
by
4.2k points

2 Answers

1 vote

Answer:

A)(x+2)(x+3)

B)(x + 2) (x + 3) = 0

x + 2 = 0

x = -2

x + 3 = 0

x = -3

Explanation:

User Maximusdooku
by
4.7k points
5 votes

Answer:

a. (x+2)(x+3)

b. x = -2

x = -3

Explanation:

a.

split 5x into 2x + 3x

then, you get

x² + 2x + 3x + 6

Split into (x² + 2x) + (3x + 6)

factorize individual groups

x (x + 2) + 3 (x + 2)

combine x + 3

your final answer is

(x + 2) (x + 3)

b.

if (x + 2) (x + 3) = 0

then (x+2) = 0 and (x+3) = 0

x + 2 = 0

x = -2

x + 3 = 0

x = -3

User Dieuhd
by
5.1k points